Contribution to the study of Triatominae in Peru: Geographic distribution, nomenclature and taxonomic notes - Chávez, Julio (2006)
Objectives: To determine the number of valid species, geographical distribution, synonymies, nomenclature and taxonomic commentaries of the Triatominae subfamily. Materials and Methods: Using the references presented below we collected the list of scientific names and geographical distribution of Triatominae existing in Peru. Results: There are 18 species of Triatominae sub-family in Peru distributed in 23 departments and grouped in 4 main tribes and 8 genders. Conclusions: It is necessary to perform ecology, morphology, molecular biology and epidemiology studies for a precise identification of the Triatominae species existing in Peru.